The hagiographies of Pierre Michon: Rimbaud le fils - Jefferson, A (Oxford University Press, 2004)
The premiss of this article is that the concern with the literary as an issue of 'radical uncertainty' has shifted from theory as polemic to the new forms of 'life-writing' that have emerged in France over the past three decades. It explores the quasi-biographical modes through which this concern is expressed in the work of Pierre Michon, concentrating in particular on the model of the lives of the saints. Focusing on Rimbaud le fils (1991), various hagiographical strategies are identified in the construction and narration of the text, and in the positioning of both author and reader in the posture of devotion. There is, however, a counterweight to this devotion in the powerful strand of derision that runs through Michon's text, whose various expressions are identified in terms of both content and authorial rhetoric. This combination of devotion and derision is best viewed as a symptom of the impossibility, both for his various contemporaries and for the modern reader, of adequately recognizing and characterizing Rimbaud's poetic 'grace'. It is by means of this problematic contemplation of the life of Rimbaud that the question of 'literature' is addressed in the text.